Physical Activity versus Sedentary Behavior: Associations with Lipoprotein Particle Subclass Concentrations in Healthy Adults - Aadland, Eivind; Andersen, John Roger; Anderssen, Sigmund Alfred; Kvalheim, Olav Martin (PLOS ONE, 2013)
BackgroundPhysical activity (PA) and sedentary behavior (SED) may have independent effects on health and disease. This might be due to PA and SED having distinct effects on lipoprotein metabolism. The aim of this study was to determine associations between lipoprotein subclass particle concentrations (-P) and accelerometer-measured SED and moderate-to-vigorous PA (MVPA) in a sample of healthy adult subjects. MethodsLipoprotein subclass particle concentrations were determined by proton nuclear magnetic resonance spectroscopy, whereas SED and MVPA were measured using Agtigraph GT1M and GT3X+ accelerometers. We obtained valid data in 73 subjects (30 men and 43 women, age 40.5 ± 10.6 years; body mass index 24.0 ± 2.8). Multiple regression analysis was used to determine associations (partial correlations) with lipoproteins. ResultsPositive associations were detected between SED and small VLDL-P, large LDL-P and TG (partial r = 0.24 to 0.25, p < .047). Corresponding associations were non-significant for MVPA (partial r = -0.12 to 0.04, p > .355). On the contrary, MVPA was positively associated with large HDL-P, average HDL size, Apo A1 and HDL-cholesterol (partial r = 0.28 to 0.50, p < .027), whereas SED was not (partial r = -0.06 to 0.07, p > .607). ConclusionThere might be a specific effect of SED versus MVPA on lipoprotein metabolism. However, our results must be interpreted carefully due to possible effect-modification by gender and a low sample size. Thus, our findings should be viewed as preliminary.